Compensation as an Economic Driver in Enhancing Employee Performance Through Work Discipline: A Study of Logistic Industry - Gautama, A.A Ngurah Restu; Putra, Kadek Budi Adnyana (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of work discipline on employee performance with compensation as a moderating variable at PT Indah Logistik Cargo, Denpasar Branch. In a competitive business environment, employee performance is a key driver of organizational success and is influenced by various internal factors, one of which is work discipline. However, the strength of this influence may be amplified or weakened by other variables such as compensation. This research employs a quantitative approach, with data collected through questionnaires distributed to 45 employees. The data were analyzed using Structural Equation Modeling (SEM) based on the Partial Least Squares (PLS) method. The findings reveal that work discipline has a positive and significant effect on employee performance. Compensation also shows a positive and significant effect on performance and serves as a moderating variable that strengthens the relationship between work discipline and employee performance. The effect of work discipline becomes more pronounced when supported by a fair and appropriate compensation system. These findings suggest that companies should consistently enforce work discipline and ensure equitable compensation as strategic efforts to enhance employee performance. This study is expected to serve as a reference for human resource management policy development, particularly in the logistics service sector.